SISTEM PEMILU, TANTANGAN BANGSA, DAN KOMUNIKASI POLITIK CALON PRESIDEN 2024-2029 - Sabarudin, Didin (UKRI, 2024)
The simultaneous presidential and legislative elections show a shift in orientation from party-centered politics to candidate-centered politics, where candidates/figures are the main object of the 2024 election compared to the previous two separate elections. Changes in the election format mean that each presidential candidate carries out political communication in various forms of tools, media, and massive campaign activities. As The candidate-centered politics, the coalition of H. Anies Rasyid Baswedan, Ph.D. - Dr. (HC) H.A. Muhaimin Iskandar promotes change, H. Prabowo Subianto - Gibran Rakabuming Raka, Advanced Indonesia, and H. Ganjar Pranowo, S.H., M.I.P - Prof. Dr. H. Moh. Mahfud is a Superior Indonesia is the tagline of the vision of each presidential candidate, namely: Fair, Prosperous Indonesia for All, Together Indonesia Progresses Towards a Golden Indonesia 2045, and Fast Movement Towards a Superior Indonesia. The successful political communication of the presidential candidates had an electoral influence and impact on the presidential election competition, which was won by the pair H. Prabowo Subianto-Gibran Rakabuming Raka according to the recapitulation of the KPU's preliminary calculations after three days of voting. This public trust is a challenge for the President-elect to resolve society's multidimensional problems in the economic fields regarding poverty and unemployment, education and health, and social welfare. The interpretive analysis of the qualitative descriptive method in this study is an understanding/meaning of people's choices regarding candidate-centered politics from the many phenomena that are constructed into a shared reality. Keywords: Election Format, Political Communication, President